Determinants of financial loss aversion: The influence of prenatal androgen exposure (2D:4D). (15th October 2017) - Hermann, Daniel
Abstract: Loss aversion is allegedly one of the key drivers for behavioral biases in the financial economics context, e.g. the disposition effect and the equity premium puzzle. However, while loss aversion is important, little research has investigated its determinants. Therefore, loss aversion was elicited using an incentivized task. Results reveal that lower loss aversion is associated with greater prenatal testosterone exposure, as measured by the 2D:4D. Surprisingly, this correlation between loss aversion and the digit ratio only holds true for the right hand. Furthermore, a greater number of siblings, improved math skills and the male gender are all associated with reduced loss aversion. The results contribute to the understanding of loss aversion in general and the effect of prenatal testosterone on economic preferences in particular. Highlights: With decreasing 2D:4D of the right hand, loss aversion is decreasing. Social value orientation is not related to loss aversion. Males reveal less loss aversion than females. Increasing self-reported math grade and number of siblings, loss aversion decreases.